Clinical Significance of Continuable Treatment with Nintedanib Over 12 Months for Idiopathic Pulmonary Fibrosis in a Real-World Setting - Kato M; Sasaki S; Tateyama M; Arai Y; Motomura H; Sumiyoshi I; Ochi Y; Watanabe J; Ihara H; Togo S; Takahashi K (Dove Medical Press, 2021)
Motoyasu Kato,1 Shinichi Sasaki,1,2 Misa Tateyama,1 Yuta Arai,1 Hiroaki Motomura,1 Issei Sumiyoshi,1 Yusuke Ochi,1 Junko Watanabe,1 Hiroaki Ihara,1 Shinsaku Togo,1 Kazuhisa Takahashi1 1Department of Respiratory Medicine, Juntendo University Graduate School of Medicine, Tokyo, Japan; 2Department of Respiratory Medicine, Juntendo University Urayasu Hospital, Urayasu, Chiba, JapanCorrespondence: Motoyasu KatoDepartment of Respiratory Medicine, Juntendo University, Graduate School of Medicine, 3-1-3 Hongo, Bunkyo-Ku, Tokyo 113-8431, JapanTel +81-3-5802-1063Fax +81-3-5802-1617Email mtkatou@juntendo.ac.jpPurpose: The INPULSIS-ON study suggested the safety and tolerability of long-term nintedanib treatment for idiopathic pulmonary fibrosis (IPF). However, there are no real-world studies on long-term nintedanib treatment. The main aim of the study was to investigate the efficacy and the tolerability of long-term treatment with nintedanib for IPF in clinical practice.Patients and Methods: This retrospective study enrolled 104 IPF patients who underwent treatment with nintedanib. Among these patients, 51 were able to receive nintedanib for more than 12 months (ie, treatment with nintedanib over 12 months was possible [P group]) and 53 were not able to receive nintedanib for more than 12 months (ie, treatment with nintedanib over 12 months was impossible [I group]). The tolerability and efficacy of nintedanib were compared between the two groups.Results: In the I group, 29 patients were unable to continue nintedanib therapy because of adverse effects, including diarrhea and nausea/anorexia. In addition, 19 and four patients could not continue nintedanib treatment because of IPF progression and worsening of performance status (PS), respectively. One patient suddenly died during nintedanib treatment. The incidence of nausea/anorexia in the I group was significantly higher than in the P group (49.06 vs 25.49%). The survival time was significantly longer in the P group than in the I group (35 vs 12 months). The decline in forced vital capacity was significantly larger in the I group than in the P group (165 vs 10 mL/year). Poor PS at nintedanib initiation was the only significant risk factor for nintedanib treatment discontinuation over 12 months. Finally, the survival time was significantly longer in patients with good PS than in those with poor PS (27 vs 13 months).Conclusion: Poor PS can result in discontinuation of nintedanib after 12 months. Long-term nintedanib treatment may be effective for survival.Keywords: idiopathic pulmonary fibrosis, nintedanib, real-world setting, performance status, nausea